Theological Value of Arabic Calligraphy Art in the Formation of Religious Character in Islamic Boarding Schools - Ristia, Muhib Ali Hasan; Haris, Abd; Kurniasih, Apri; Afroyim, Kunainah; Isro, Arsan; Damanhuri, Damanhuri; Asy’arie, Bima Fandi (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to identify the theological values ​​embedded in the study of Arabic calligraphy and to contribute to the formation of the religious character of Islamic boarding school students. Methodology: This study employed an interpretive research paradigm with a qualitative approach, conducted through interviews with 12 teachers (ustadz) and focus group discussions (FGD) with 6 students. The data obtained were analyzed using qualitative content analysis techniques. Furthermore, the researchers conducted observations and document analysis to strengthen the data presented. Main Findings: The findings of this study indicate that theological values ​​in Arabic calligraphy are integrated into three main aspects: spirituality, Islamic aesthetics, and morality. In the spiritual aspect, the values ​​of tauhidiyah (monotheism), ikhlas (sincerity), dhikrullah (remembrance of Allah), tadabbur (religious service), and tazkiyatul nafsi (observance of one's soul) are found. In the Islamic aesthetic, the values of jamal (community), creativity, patience, and perseverance are essential to the learning process. In the moral aspect, calligraphy instills amanah (trustworthiness), tawadhu' (religious tolerance), and ukhuwah (brotherhood). Learning Arabic calligraphy contributes to strengthening spirituality, forming personal morals, instilling etiquette, developing Islamic aesthetics, and strengthening students' socio-religious character. Novelty/Originality of this study: The novelty of this study has contributed to the strengthening of arts-based Islamic education that integrates theological values, aesthetic practices, and holistic character formation in a sustainable manner. This research has implications suggesting that Arabic calligraphy can be used as an effective pedagogical instrument for shaping socio-religious character education for students in Islamic boarding schools.